2004
DOI: 10.1002/pssa.200306720
|View full text |Cite
|
Sign up to set email alerts
|

UV-emitting phosphors: synthesis, photoluminescence and applications

Abstract: UV‐emitting phosphors find uses in various applications, such as photocopying, phototherapy, sun tanning, etc. The phosphor requirements for these applications vary. Simple methods for preparing different UV‐emitting phosphors are described. Novel syntheses for some borates (SrB4O7:Eu, CeMgB5O10:Gd, GdBO3:Pr, LaB3O6:Ce,Bi, LaB3O6:Gd,Bi, LaB3O6:Ce, Ba2B5O9Cl:Eu), a silicate (Ba2SiO5:Pb), phosphates (Sr2−xMgxP2O7:Eu) and a sulphate (CaSO4:Eu) are reported. Photoluminescence spectra of the phosphors so prepared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…UV-emitting phosphors have been also reported in the context of their applications (e.g., some borates, silicate, phosphates and sulphate), but their decay times are very short [22]. Borate phosphors with high efficiency, easy processibility, durability and long afterglow have attracted attention [23,24], including blue-emitting Ce-activated calcium aluminoborate [25].…”
Section: Introductionmentioning
confidence: 99%
“…UV-emitting phosphors have been also reported in the context of their applications (e.g., some borates, silicate, phosphates and sulphate), but their decay times are very short [22]. Borate phosphors with high efficiency, easy processibility, durability and long afterglow have attracted attention [23,24], including blue-emitting Ce-activated calcium aluminoborate [25].…”
Section: Introductionmentioning
confidence: 99%
“…Among the diphosphates, SrM II P 2 O 7 (M = Mg, Cr, Cu) have shown interesting relationships among chemical constitution, crystal structure, and luminescence properties (7). SrMgP 2 O 7 -based compounds are known to be efficient phosphors (8)(9)(10) and as corrosion inhibitor pigments (11,12). The biocompatibility of calcium pyrophosphate (Ca 2 P 2 O 7 , CPP) has been demonstrated in numerous experiments; in addition, it was shown that CPP possesses osteostimulating and bioresorptive properties (13).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the narrowband ultraviolet B radiation is used for curing many types of skin disorders. Also gadolinium activated crystallite has attracted considerable research interest owing to its UV emission in a narrow region (300-320) [8]. This narrow region showed remarkable therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%